2018
DOI: 10.17222/mit.2017.178
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency perovskite solar cells improved with low-cost orthorhombic Cu2ZnSnS4 as the hole-transporting layer

Abstract: Quaternary copper chalcogenide Cu2ZnSnS4 (CZTS) nanoparticles (NPs) were synthesized with the sol-gel technique and used as the hole-transporting layer (HTL), achieving a power-conversion efficiency (PCE) of 13.41 %, which is the highest PCE for Cu-based inorganic HTLs. The effects of the CZTS HTL on the optical absorption, crystallinity, crystal plane orientation and hysteresis of the J-V curve for the devices with a perovskite film were investigated and compared with spiro-OMeTAD, revealing the role of CZTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…They found a PCE of 13.41% with a V oc of 0.962 V, a J sc of 22.43 mA/cm 2 , and an FF of 62%. Kesterite CZTS exhibited a slightly poor performance compared to its wurtzite counterpart, which can be due to the lower carrier concentration and higher resistivity . Yuan et al performed an investigation on band-gap tuning of CZTS quantum dots by replacing sulfur with selenium and studied its influence on the performance of n-i-p PSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a PCE of 13.41% with a V oc of 0.962 V, a J sc of 22.43 mA/cm 2 , and an FF of 62%. Kesterite CZTS exhibited a slightly poor performance compared to its wurtzite counterpart, which can be due to the lower carrier concentration and higher resistivity . Yuan et al performed an investigation on band-gap tuning of CZTS quantum dots by replacing sulfur with selenium and studied its influence on the performance of n-i-p PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Kesterite CZTS exhibited a slightly poor performance compared to its wurtzite counterpart, which can be due to the lower carrier concentration and higher resistivity. 27 Yuan et al performed an investigation on band-gap tuning of CZTS quantum dots by replacing sulfur with selenium and studied its influence on the performance of n-i-p PSCs. Although the S substitution with Se significantly reduces the film resistivity and improves the charge separation at the interface, J−V results confirm that CZTSe and CZTS have similar J sc values (∼19 mA/cm 2 ) and V oc is considerably reduced.…”
Section: Introductionmentioning
confidence: 99%
“…So far, properties of micrometric and sub-micrometric (>0.5 μm) CZTS thin films fabricated using several different methods have been extensively studied [7,23,24,25,26] with the purpose of being the absorber layer in solar cell. There are also studies on CZTS thin films with <0.5 μm thickness, in which they are used as a transport layer in a perovskite solar cell [27,28,29]. However, their focus is on the application of the thin film in the solar cell, with limited information on properties.…”
Section: Introductionmentioning
confidence: 99%
“…[ 127 ] Kesterite CZTS/Se material has exhibited good potential as HTL for PSCs, as they exhibit suitable optoelectronic properties. [ 128 ] Wu et al [ 129 ] reported CZTS nanoparticles (NPs) as HTL for CH 3 NH 3 PbI 3 PSCs using the spin‐coating method and achieved a PCE of 12.75%. They observed an increase in J sc (20.54 mA cm −2 ) due to enhanced light absorption in the visible (400–850 nm) region after applying CZTS as HTL.…”
Section: Applications Of Kesteritesmentioning
confidence: 99%